(untitled) (Simbiótica. Revista Eletrônica, 2023)
The Chronicle invites you to learn a little about the life of Marina, a young woman with a poor background, born in a northeast town. Inspired by the strength and struggle of many women scientists and teachers, the story tells about the many struggles to become and act as a science teacher in a dystopian country that neglects teacher training and scientific thinking. Marina’s professional journey is told from two different time frames (2015 and 2025), separated by a tragicomic event in her work environment.